An Overview of Whole Grain Regulations, Recommendations and Research across Southeast Asia - Brownlee, Iain A (Nutrients, 2018)
The Association of Southeast Asian Nations (ASEAN) is a diverse region that is experiencing economic growth and increased non-communicable disease burden. This paper aims to evaluate the current regulations, dietary recommendations and research related to whole grains in this region. To do this, a systematic literature review was carried out and information was collected on regulations and dietary recommendations from each member state. The majority of publications on whole grains from the region (99 of 147) were in the area of food science and technology, with few observational studies (n = 13) and human intervention studies (n = 10) related to whole grains being apparent. Information from six countries (Indonesia, Malaysia, The Philippines, Singapore, Thailand and Vietnam) was available. Wholegrain food-labelling regulations were only noted in Malaysia and Singapore. Public health recommendation related to whole grains were apparent in four countries (Indonesia, Malaysia, The Philippines, Singapore), while recent intake data from whole grains was only apparent from Malaysia, The Philippines and Singapore. In all cases, consumption of whole grains appeared to be very low. These findings highlight a need for further monitoring of dietary intake in the region and further strategies targeted at increasing the intake of whole grains.